Results of the West Nile Fever Agent Monitoring in the Russian Federation in 2019 and the Forecast of Epidemic Situation Development in 2020 - E. V. Putintseva; I. O. Alekseychik; S. N. Chesnokova; S. K. Udovichenko; N. V. Boroday; D. N. Nikitin; E. A. Agarkova; A A. Baturin; I. M. Shpak; V. K. Fomina; A. V. Nesgovorova; V. P. Smelyansky; et al. (Проблемы особо опасных инфекций, 2020)
The trend towards an increase in the West Nile fever incidence among the population in the Russian Federation, recorded in the season of 2018, continued and led to a significant increase in the incidence in 2019 (the indicator was 2 times higher than the long-term average). The features of manifestations of the epidemiological process of WNF in 2019 were identified: early registration of cases of the disease, activation of natural and natural-anthropourgic foci in the Southern Federal District (90 % of the total incidence in the Russian Federation), an increase in the share of neuro-invasive forms, dominance of patients aged 50 and older in the structure of the incidence, late epidemic season ending. It was established that in the season of 2019, the lineage 2 of WNV circulated in the European part of Russia. In the Volgograd Region, simultaneous presence of the West Nile virus and Sindbis virus in mosquitoes Culex pipiens and Culex modestus was identified. It was shown that the most significant factors for predicting the epidemiological situation on West Nile fever in the Volgograd Region are the average seasonal summer air temperature and monthly average indicators of relative humidity in the spring and summer periods, and the average monthly air temperatures in the spring and summer in the Rostov Region. In the Astrakhan Region, a significant correlation dependence of the influence of the considered factors on the incidence of the population has not been established. The forecast of the development of epidemic situation in 2020 does not exclude a possible increase in the incidence in the territories of the European part of Russia, endemic for West Nile fever, and the occurrence of local outbreaks in individual constituent entities, if the complex of climatic conditions and social factors favorable for West Nile virus coincide.